Tradisi Cecce’an dan Polean dengan Prinsip Ka’buka’an dalam Pernikahan Perspektif Akuntansi: Studi Etnografi Masyarakat Situbondo - Lailatul Istiqomah; Rahmawati Rahmawati; Revi Septia; Maimuna Maimuna (Jurnal Akuntansi Terapan dan Bisnis, 2023)
This research focuses on accountability and transparency that occurs in the Cecce'an and Polean traditions with the Ka'buka'an principle in the marriage customs of the Situbondo community. The research design used is a qualitative method with an ethnographic study approach. The selection of informants used in this research was based on the snowball sampling method. Researchers are looking for informants who know the research process and materials as key informants, namely the Situbondo people who apply Cecce'an and Polean traditions at wedding ceremonies. The results of the research show that the people of Situbondo believe that there is a meaning contained in the Cecce'an and Polean traditions seen from an accounting perspective, namely the meaning of debts and receivables. The Situbondo community in its wedding tradition also applies a system of recording and broadcasting the amount and type of donations as a form of accountability and transparency.